Recent Advances in Non‐nucleophilic Mg Electrolytes - Wu, Qijie; Shu, Kewei; Sun, Lili; Wang, Haihua (Frontiers in Materials, 2021)
High-performance electrolyte is still a roadblock for rechargeable Mg batteries development. Grignard type electrolytes were once the only choice in the early stage of rechargeable Mg batteries research. However due to their nucleophilic nature and high reactivity, Grignard type electrolytes have inherent safety issues and low oxidation stability, which restricts the development of rechargeable Mg batteries in terms of practical application. Recently emerging novel Mg battery systems such as Mg-S, Mg-O2/air battery also require non-nucleophilic electrolytes with high oxidation stability. This short review summarizes recent advances in non-nucleophilic Mg electrolytes, and aims to provide insights into electrochemical properties and active Mg ion structure of such electrolytes.